Endoscopic versus microscopic stapes surgery outcomes A meta-analysis and systematic review - Koukkoullis Alexandros; Tóth István; Gede Noémi; Szakács Zsolt; Hegyi Péter; Varga Gábor; Pap István; Harmat Kinga; Németh Adrienn; Szanyi István; Lujber László; Gerlinger Imre; et al. (2020)
Compare intraoperative and postoperative outcomes of endoscopic and microscopic stapes surgery to provide objective evidence on whether the former is a better alternative than the latter.We performed a systematic review and meta-analysis for studies that compared endoscopic stapes surgery with microscopic stapes surgery. Only studies that met predetermined criteria were selected and assessed for bias and quality. Primary outcomes were postoperative air-bone gap (ABG) and chorda tympani nerve injury. Secondary outcomes were average operating time, tympanic membrane (TM) perforation, and postoperative taste disturbance, pain, and dizziness. We calculated pooled odds ratios (ORs) with 95% confidence intervals (CIs) for dichotomous outcomes and weighted mean difference (WMD) with 95% CI for continuous outcomes. A confidence interval starting above 1.0 was considered as statistically significant. I2 and χ2 tests were used to quantify statistical heterogeneity. We used funnel plots to look for publication bias and performed a sensitivity analysis.Six nonrandomized cohort studies were eligible. The primary outcomes were ABG < 10 dB: OR = 1.80 (95% CI: 0.96 to 3.38), ABG = 11 dB to 20 dB: OR = 1.49 (95% CI: 0.76 to 2.93), ABG > 20 dB: OR = 2.51 (95% CI: 0.77 to 8.22), and chorda tympani injury: OR = 3.51 (95% CI: 1.55 to 7.93). Secondary outcomes were taste: OR = 2.36 (95% CI: 1.01 to 5.51), average operation time: WMD = 0.14 (95% CI: -11.69 to 11.98), TM perforation: OR = 1.70 (95% CI: 0.44 to 6.58); pain: OR = 0.84 (95% CI: 0.36 to 1.96), and dizziness: OR = 2.15 (95% CI: 0.94 to 4.89).Endoscopic stapes surgery is a valid alternative to the microscope.2a Laryngoscope, 2019.